Bioactive compounds, minerals and antioxidants of edible flowers of peach and apple - Marisela Calderón-Jurado; Oscar Cruz-Álvarez; Porfirio Juárez-López; Ofelia Adriana Hernández-Rodríguez; Laura Raquel Orozco-Meléndez; Emilio Raymundo Morales-Maldonado; Damaris Leopoldina Ojeda-Barrios; Irán Alia-Tejacal (International Journal of Food Properties, 2023)
Peach and apple flowers were evaluated for their human nutritional value by obtaining baseline information on their contents of bioactive compounds, minerals and antioxidant capacity. We used simple random sampling and nested statistical analysis to examine flowers of three peach cultivars (“July Flame,” “Cary Mac” and “Fair Time”) and two crab apple cultivars (“Manchurian” and “John Downie”). Flowers of “John Downie” stood out for their high contents of ash, protein and crude fat. Carbohydrate contents were highest for “Fair Time” and “Cary Mac.” Peach and apple differed in their contents of total phenols (73.23 ± 1.94 mg GAE/g peach and 86.65 ± 1.18 mg GAE/g, apple) and total flavonoids (TFl) (5.29 ± 0.10 mg QE/100 g peach and 7.99 ± 0.3 mg QE/100 g apple). The peach cultivar “Fair Time” and the crab apple cultivars “Manchurian” and “John Downie” showed the highest values of K+ and Mg2+. Micronutrient concentrations differed between species, however, Zn2+ and Na+ values were similar among species but differed between cultivars. Antioxidant capacity showed inter-species variations with the methods ABTS and FRAP. The results indicate a good potential for both peach and apple flowers to be incorporated in the human diet, for fresh consumption as functional foods.